The Kazakh Text as a Cultural Supertext - Abisheva, S.; Khavaidarova, M.; Atebayeva, G.; Serikova, S.; Baibolov, A. (Journal of Cultural Analysis and Social Change, 2026)
The concept of "Kazakhstani text" in modern humanities is gradually emerging as an independent analytical category, reflecting the totality of artistic, cultural, and historical-memorial representations of Kazakhstan in the literature of the late 20th and early 21st centuries. In the context of globalization, transnational mobility, and post-Soviet transformations, Kazakhstani literature is becoming a space for complex dialogue between national tradition and a multilingual, multicultural context, which highlights the need for a theoretical understanding of the specifics of this textual formation. The aim of this article is to identify the structural, semantic, and poetic characteristics of the Kazakhstani text as a special type of culturally marked hypertext. The study establishes that the Kazakhstani text is not reducible to a geographical or ethnographic description of a territory, but rather represents a complex model of the artistic exploration of space, in which national history, traumatic experience, and the memory of nomadic culture and the Soviet past are reinterpreted within the coordinates of modernity. It is concluded that the Kazakhstani text functions as a crucial mechanism for cultural self-identification and the transmission of national experience in a global literary context.